2011
DOI: 10.1111/j.1365-2966.2011.19903.x
|View full text |Cite
|
Sign up to set email alerts
|

On the correlations between galaxy properties and supermassive black hole mass

Abstract: We use a large sample of upper limits and accurate estimates of supermassive black hole (SMBH) masses coupled with libraries of host galaxy velocity dispersions, rotational velocities and photometric parameters extracted from Sloan Digital Sky Survey i-band images to establish correlations between the SMBH and host galaxy parameters. We test whether the mass of the black hole, M_bh, is fundamentally driven by either local or global galaxy properties. We explore correlations between M_bh and stellar velocity di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
270
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(311 citation statements)
references
References 147 publications
34
270
4
Order By: Relevance
“…Furthermore, many galaxies host both a classical and a pseudo-bulge (e.g., Erwin et al 2003Erwin et al , 2015Athanassoula 2005;Gadotti 2009;MacArthur et al 2009;Erwin 2010;dos Anjos & da Silva 2013;Seidel et al 2015). In the recent literature, pseudo-and classical bulges have frequently been divided at the Sérsic index n 2 sph = (e.g., Sani et al 2011;Beifiori et al 2012), although, from a selection of hundreds of disk galaxies imaged in the Kband, Graham & Worley (2008) observed no bimodality in the bulge Sérsic indices about n 2 sph = or any other value. While pseudo-bulges are expected to have exponential-like surface brightness profiles (n 1 sph  ), being disky components that formed from their surrounding exponential disks (e.g., Bardeen 1975;Hohl 1975;Combes & Sanders 1981;Combes et al 1990;Pfenniger & Friedli 1991), it has been shown that mergers can create bulges with n 2 sph < (e.g., Eliche-Moral et al 2011;Scannapieco et al 2011;Querejeta et al 2015), just as low-luminosity elliptical galaxies (not built from the secular evolution of a disk) are also well known to have n 2 sph < and even n 1 sph < (e.g., Davies et al 1988;Young & Currie 1994;Jerjen et al 2000).…”
Section: Pseudo-versus Classical Bulgesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, many galaxies host both a classical and a pseudo-bulge (e.g., Erwin et al 2003Erwin et al , 2015Athanassoula 2005;Gadotti 2009;MacArthur et al 2009;Erwin 2010;dos Anjos & da Silva 2013;Seidel et al 2015). In the recent literature, pseudo-and classical bulges have frequently been divided at the Sérsic index n 2 sph = (e.g., Sani et al 2011;Beifiori et al 2012), although, from a selection of hundreds of disk galaxies imaged in the Kband, Graham & Worley (2008) observed no bimodality in the bulge Sérsic indices about n 2 sph = or any other value. While pseudo-bulges are expected to have exponential-like surface brightness profiles (n 1 sph  ), being disky components that formed from their surrounding exponential disks (e.g., Bardeen 1975;Hohl 1975;Combes & Sanders 1981;Combes et al 1990;Pfenniger & Friedli 1991), it has been shown that mergers can create bulges with n 2 sph < (e.g., Eliche-Moral et al 2011;Scannapieco et al 2011;Querejeta et al 2015), just as low-luminosity elliptical galaxies (not built from the secular evolution of a disk) are also well known to have n 2 sph < and even n 1 sph < (e.g., Davies et al 1988;Young & Currie 1994;Jerjen et al 2000).…”
Section: Pseudo-versus Classical Bulgesmentioning
confidence: 99%
“…The red dashed line indicates the BCES bisector linear regression for the bulges of the 45 early-type galaxies (E+S0), with the red shaded area denoting its 1s uncertainty. Beifiori et al 2012;Erwin & Gadotti 2012).…”
Section: Black Hole Mass-spheroid Stellar Massmentioning
confidence: 99%
See 1 more Smart Citation
“…very massive central super-massive black hole. Empirically, black hole masses correlate most strongly with the velocity dispersion (Beifiori et al 2012), with the largest reported masses from dynamical studies being (1-2)×10 10 M ⊙ , e.g. in the BCGs NGC 3842 and NGC 4889 (McConnell et al 2011) and in the field elliptical NGC 1600 (Thomas et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We assign to each merging galaxy pair two SBHs with masses drawn from 13 different SBH-galaxy relations found in the literature (Häring & Rix 2004;Gültekin et al 2009;Sani et al 2011;Graham et al 2011;Graham 2012;Graham & Scott 2013;Beifiori et al 2012;McConnell & Ma 2013;Kormendy & Ho 2013), spanning a broad range of uncertainty and including recent observations that corrected SBH estimates upwards.…”
Section: Observationally-based Gw Simulationsmentioning
confidence: 99%